Compreensões de aprendizes acerca do processo de aprendizagem de LE mediada pela música - Molesin, Claudete Alves da Silva (Universidade Federal de São Carlos, 2020)
This qualitative and exploratory study aims to analyze the perspectives of a group of foreign language learners about what they claim to have learned from the English language, mostly through music and without the mediation of a teacher. In addition, we seek to find out how these students explain the English language learning, seeking to recognize the interfaces between their statements and their strategies for learning the target language. To this end, we rely on studies on the approach and / or culture of learning languages conducted by Almeida Filho (2010, 2014 and 2015) and which address precepts or practices underlying the act of learning a Foreign Language. We focus, through the studies of Ferraço de Paula (2008), on the spontaneous competence of learning languages whose approach is determined by the traditions of learning and reflected in the practices and habits of studying. We were also interested in investigating how factors such as learning strategies, Oxford (2003), used by the research participants reflect their culture of learning languages. Other fundamentals and concepts, likewise, served as supporting pillars for the development of this study, such as motivation in the context of foreign language learning, Gardner (2005, 2010, 2012) and Deci and Ryan (1975, 2000). Studies by other researchers also contributed to the composition of the theoretical framework. To the data production, this research included a semi-structured questionnaire and an interview script that guided us in conducting this study. Through data analysis, the following results can be obtained: language spontaneous competence is evident in the procedures demonstrated by the participants. The recognition of the culture of learning languages and the learning strategies adopted by these learners influenced by their peculiar styles of learning and by an intrinsic orientation allowed us to glimpse their attitudes, beliefs and motivations in conducting their autonomous learning.
Learner's understanding about the music-mediated foreeign language learning process
Keywords: Cultura de aprender línguas; Estratégias de aprendizagem; Motivação; Música; Language learning culture; Learning strategies; Motivation; Music; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM